Comparison of outcomes with multifocal intraocular lenses: a meta-analysis - Béatrice Cochener (Dove Medical Press, 2011)
Béatrice Cochener1, Antoine Lafuma2, Babak Khoshnood2, Laurène Courouve2, Gilles Berdeaux3,41Centre Hospitalier Universitaire Brest, Brest, France; 2Cemka Eval, Bourg la Reine, France; 3Alcon France, Rueil-Malmaison, France; 4Conservatoire National des Arts et Métiers, Paris, FrancePurpose: To compare the clinical outcome of different multifocal intraocular lenses (IOLs) based on information reported in the international literature.Methods: All comparative clinical trials that involved implanting at least one multifocal IOL in patients with cataract or presbyopia were extracted from the literature. Clinical outcomes included uncorrected near visual acuity, uncorrected distance visual acuity, visual acuity, spectacle independence, and halos. Random effects meta-analyses were conducted to compare outcomes for the different IOL types.Results: Twenty papers were identified describing 11 monofocal IOLs and 35 multifocal IOLs (19 diffractive, including 12 ReSTOR®, 14 refractive, and two accommodative) patient cohorts. Multifocal and monofocal uncorrected distance visual acuity was 0.165 (0.090–0.240) and 0.093 (0.088–0.098), respectively. Compared with monofocal IOLs, multifocal IOLs produced better uncorrected near visual acuity (0.470 [0.322–0.618] versus 0.141 [0.131–0.152]; P < 0.0001), resulting in higher spectacle independence (incidence rate ratio [IRR] 3.62 [2.90–4.52]; P < 0.0001). Compared with refractive multifocal IOLs, diffractive multifocal IOLs produced a similar uncorrected distance visual acuity (0.105 [0.098–0.111] versus 0.085 [0.029–0.140]; P ≤ 0.78, not significant) and better uncorrected near visual acuity (0.217 [0.118–0.317] versus 0.082 [0.067–0.098]; P < 0.0001) resulting in higher spectacle independence (IRR 1.75 [1.24–2.48]; P < 0.001). Compared with other multifocal IOLs, ReSTOR produced a better uncorrected distance visual acuity (0.067 [0.059–0.076] versus 0.093 [0.088–0.098]; P < 0.0001) and better uncorrected near visual acuity (0.064 [0.046–0.082] versus 0.141 [0.131–0.152]; P < 0.006), resulting in higher spectacle independence (IRR 2.06 [1.26–1.36]; P < 0.004). Halo incidence rates with different types of multifocal implants did not differ significantly.Conclusion: Multifocal IOLs provide better uncorrected near visual acuity than monofocal IOLs, leading to less need for spectacles. Multifocal IOL design might play a role in postsurgical outcome, because better results were obtained with diffractive lenses. ReSTOR showed better uncorrected near visual acuity, uncorrected distance visual acuity, and higher spectacle independence rates compared with other multifocal IOLs.Keywords: multifocal implants, meta-analysis, uncorrected near visual acuity, uncorrected distance visual acuity, spectacle independence, patient satisfaction